Psychiatrie, genre et sexualités dans la seconde moitié du XXe siècle - Arena, Francesca; Chiletti, Silvia; Coffin, Jean-Christophe (Comment s'en sortir?, 2015)
Les diagnostics cliniques et les différentes nosographies psychiatriques qui ont été établies dans la deuxième moitié du XXe siècle, notamment dans les différentes éditions du manuel américain de diagnostic et statistique des troubles mentaux (DSM), montrent qu'un nombre très significatif de troubles sont envisagés comme étant genrés. Plusieurs controverses ont marqué l'histoire de ces diagnostics depuis les années 1950 : d'abord celui des sexualités et de leurs frontières floues, ensuite la notion controversée d'identité de genre, enfin la problématique des troubles périnataux. Si le principe de différentiation constitue un élément incontournable de la pensée psychiatrique, le façonnage et l'usage du concept de « genre » révèlent des tensions entre la psychiatrie et la société (notamment les mouvements gay, féministes et trans) mais aussi au sein de la psychiatrie elle-même. Il apparaît évidant que, dans les classifications psychiatriques, les normes sociales de genre sont intégrées de manière passive et acritique, au point que l'usage du concept de genre peut amener à l'inverse à renforcer la naturalisation des comportements alors même que, dans les sciences sociales, il est utilisée pour interroger et déconstruire la prétendue naturalité de la différence des sexes.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; sofia; systèmes d'oppressions; thématiques; violences; états-unis

Food and femininity - Cairns, Kate; Johnston, Josée (Bloomsbury Academic, 2015)
"Over the space of a few generations, women's relationship with food has changed dramatically. Yet – despite significant advances in gender equality – food and femininity remain closely connected in the public imagination as well as the emotional lives of women. While women encounter food-related pressures and pleasures as individuals, the social challenge to perform food femininities remains: as the nurturing mother, the talented home cook, the conscientious consumer, the svelte and health-savvy eater. In Food and Femininity, Kate Cairns and Josée Johnston explore these complex and often emotionally-charged tensions to demonstrate that food is essential to the understanding of femininity today. Drawing on extensive qualitative research in Toronto, they present the voices of over 100 food-oriented men and women from a range of race and class backgrounds. Their research reveals gendered expectations to purchase, prepare, and enjoy food within the context of time crunches, budget restrictions, political commitments, and the pressure to manage health and body weight. The book analyses how women navigate multiple aspects of foodwork for themselves and others, from planning meals, grocery shopping, and feeding children, to navigating conflicting preferences, nutritional and ethical advice, and the often-inequitable division of household labour. What emerges is a world in which women's choices continue to be closely scrutinized – a world where 'failing' at food is still perceived as a failure of femininity. A compelling rethink of contemporary femininity, this is an indispensable read for anyone interested in the sociology of food, gender studies and consumer culture."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; inégalités; ontario; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques; toronto; travail

Care, environnement et éthique globale - Laugier, Sandra (Cahiers du Genre, 2015)
Cet article vise à mettre en évidence la puissance transformatrice des éthiques féministes du care pour les questions environnementales, et réciproquement, à montrer comment la question environnementale est le lieu présent de redéfinition des enjeux du care . En valorisant des caractéristiques morales identifiées comme féminines — l’attention, le souci des autres — l’éthique du care a contribué à placer la vulnérabilité au cœur de la morale, mais a aussi déplacé et élargi son champ. Ce que le care peut nous apprendre sur la question environnementale, c’est que le développement de nos sociétés riches occidentales n’a été possible que par leur dépendance par rapport à une nature, à des ressources — des animaux et des humains. La crise climatique est l’occasion de repenser l’idée de développement durable à partir du care .
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; care; cours; discipline; inégalités; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; écoféminisme

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle